1988
DOI: 10.1161/01.res.63.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Certain beta-blockers can decrease beta-adrenergic receptor number: II. Down-regulation of receptor number by alprenolol and propranolol in cultured lymphoma and muscle cells.

Abstract: We have used two different cultured cell lines-S49 lymphoma cells and BC3H-1 muscle cellsto examine the regulation of /3-adrenergic receptors by receptor antagonists. Rather than an increase ("up-regulation") of receptor number that such antagonists often produce, we found that certain /3-blockers elicit a decrease ("down-regulation") of beta-adrenergic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Aarons and Molinoff [7] reported that the influence of a β-antagonist is able to increase the β-AR number in heart, lung and lymphocytes of rats after 7 days of treatment. In contrast to this observation, in membranes prepared from BC3H-1 muscle cells and in intact S49 mouse lymphoma cells, which both contain a pure population of β # -receptors, propranolol failed to increase the receptor number and elicited a substantial 20-70 % decrease in receptor number after 16-20 h of treatment [28]. In our studies, H9c2 (2-1) cells were incubated with propranolol for 24 h without any changes in either the total β-receptor level or in the β # -mRNA level.…”
Section: Discussioncontrasting
confidence: 68%
“…Aarons and Molinoff [7] reported that the influence of a β-antagonist is able to increase the β-AR number in heart, lung and lymphocytes of rats after 7 days of treatment. In contrast to this observation, in membranes prepared from BC3H-1 muscle cells and in intact S49 mouse lymphoma cells, which both contain a pure population of β # -receptors, propranolol failed to increase the receptor number and elicited a substantial 20-70 % decrease in receptor number after 16-20 h of treatment [28]. In our studies, H9c2 (2-1) cells were incubated with propranolol for 24 h without any changes in either the total β-receptor level or in the β # -mRNA level.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the eect of drug treatment on receptor density appeared dierent in other studies with dierent experimental settings. For example, Hughes et al (1988) reported downregulation of b-AR by propranolol in cultured lymphoma and muscle cells. Extrapolation of observations from such studies to the clinic is dicult and should be done with great care.…”
Section: Eects Of Long-term Treatment With Inverse Agonistsmentioning
confidence: 99%
“…However, the effect of drug treatment on receptor density appeared different in other studies with different experimental settings. For example, Hughes et al . (1988) reported downregulation of β‐AR by propranolol in cultured lymphoma and muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have not determined if the initial diminution of DHAP binding at low propranolol concentrations seen in Figure 4 represents the actual removal of binding sites from the cell surface or the prolonged occupancy of surface receptors by the antagonist. The alteration of receptor numbers in response to receptor occupancy is commonly encountered and is a crucial element in how a cell reacts to and interprets relevant stimuli (19)(20)(21)(22)(23). Both agonists and antagonists of receptor function are capable of eliciting these responses.…”
Section: Regulation Of Binding Site Number By B-blockage and Dexawethmentioning
confidence: 99%